Socialization of Analog to Digital TV Broadcast Migration as a Broadcasting Innovation in Gorontalo City based on Diffusion-Innovation Perspective - Hadjingo, Abd. Djalil W.; Subhan, Andi; Akasse, Cahyadi Saputra; Ratnasari, Dwi (Jurnal Ilmiah Mandala Education (JIME), 2024)
In this research, socialization is important in analog TV to digital TV broadcast migration under the government's policy in regulating TV broadcasting. This research aims to find out the socialization of analog TV to digital TV broadcast migration as a broadcasting innovation in Gorontalo City from the perspective of diffusion of innovation. It employs a qualitative method.  The informants taken are from three institutions related to the analog TV to digital TV broadcast migration and the public as additional informants. The data collection techniques are through observation, structured interviews, and documentation. The data analyzed are through collection, condensation, presentation, and conclusion drawing. The results of this research indicate that the socialization implemented is through five aspects of diffusion of innovation theory, namely relative advantage (digital TV is certainly superior), suitability (TV migration has been in process and known by the public), complexity (the public is considered to understand the application of digital TV), trialability (suitable to be applied in Gorontalo city area and areas without Blank Spot) and visibility (the application of analog to digital TV migration is as expected by the government and has positive value for the community). Those five aspects are seen in the socialization of analog TV to digital TV broadcast migration as a broadcasting innovation in Gorontalo City.